Procedimentos simplificados para a avaliação da envoltória pelo método prescritivo do RTQ-C, com foco em edificações existentes - Natalia Fernandes Ribeiro (2016)
The National Conservation and Rational Use of Energy Policy was established by the first Brazilian law for energy efficiency, Law no. 10,295 of 2001. As a result of this and other actions to improve energy efficiency in buildings, in 2009, there was launched the voluntary certification program for buildings. The regulation (RTQ-C) indicates technical requirements and methods to classify commercial, services and public buildings, however, after seven years of the release, the number of certificated buildings is low if compared to the number of new buildings and the extensive field already built in Brazil. This can be explained by the limitations to understand and apply the labeling methods to evaluate buildings. This thesis aims to propose simplified procedures for the determination of the variables of the buildings envelopment, related to the prerequisites and equations of the consumption indicator (ICenv), to evaluate the level of energy efficiency of existing buildings, according to the Prescriptive Method of the RTQ-C. The methodology is divided into five main stages. The first stage is an initial analysis of the studied topics and an overview of buildings certification, and the second stage is the dtermination of cases to be studied. The third stage is the simplification proposals for the variables to evaluate the buildings envelopment. The fourth stage shows the validation of the proposed simplifications, through the evaluation of case studies. For this matter was used the proposed simplified procedures and the procedures recommended by the regulation. The fifth stage consists of comparing the results achieved with the assessment by both procedures, for the variables of the ICenv, for the level of efficiency and for the evaluation term. The results achieved were the simplified procedures for the assessment of the envelopments variables: Areas (Ape, Apcob, Aenv, Atot and Vtot); thermal transmittance and absorbance of external surfaces; PAZ; PAF; FS; and shading angles (AVS and AHS). Four existing buildings were evaluated by both procedures and the results indicated that the changes were not significant, and, there was no change in the set level of efficiency. From the analysis of the time applied on the assessment of the buildings, there was a reduction greater than 80%, when the simplified procedures were applied. Therefore, from the results of this study, it is considered that the simplified procedures can be incorporated for the assessment of the buildings envelopment, according to the methods of the RTQ-C.